Preconditions for A Quality Tourism Destination Strategy as A Recognizable Tourism Product (Vallis Aurea, 2020)
This paper analyses high-quality and recognizable tourism product, the coher-ence of all involved holders of the tourism as well as a good organization in the tourism destination, a strong brand, image and how to fulfil or even exceed the tourist expectations by ensuring a recognizable tourism product that creates positive experience. The aim of this research is to define the major precondi-tions for a quality tourism destination strategy as recognizable tourism product by including experts and their experience in a focus group interview.